Nutritional quality enrichment of rice straw using Pleurotus sajor-caju (Fr.) singer and micro-filamentous fungi (Bangladesh Journal of Botany, 2014)
Solid state fermentation was carried out by Pleurotus sajor-caju, micro-filamentous fungi and culture filtrate of P. sajor-caju with different combinations to improve nutritional qualities of rice straw. The acid detergent fiber (ADF) and neutral detergent fiber (NDF) contents of the fermented rice straw were significantly reduced in mixed culture with filamentous fungi and P. sajor-caju. The cellulose and hemicellulose contents also reduced in similar manner. P. sajor-caju showed strong lignolytic activity resulting cellulose/lignin ratio of 5:1 when rice straw and PKC were supplemented. The protein content increased from 5.86 - 11.12, 12.98 and 13.14%, respectively. The maximum and significant amount of soluble protein 11.84 mg/g and glucosamine 18.50 mg/g was recorded in mixed culture at 30% palm oil kernel cake (PKC) supplementation. The maximum reducing sugar of 18.76 mg/g and endoglucanase activity 11.54 U/ml was recorded in same treatment. The mineral contents K, P, Ca, Mg and Fe were significantly higher in fermented sample while Cu and Zn were non-significant. The antioxidant activity improved by 45% and significantly varied between fermented and unfermented samples. DOI: http://dx.doi.org/10.3329/bjb.v42i2.18039 Bangladesh J. Bot. 42(2): 333-341, 2013 (December)